A ENHANCED LOGISTIC CHOATIC ENCRYPTION ALGORITHM FOR ENSURING THE SECURED DATA TRANSMISSION TO COUNERFEIT THE ATTACKS. (International Journal of Food and Nutritional Sciences, 2023)
Cloud computing is meant for storing the huge data using third party that ensures that confidential data cannot be accessed by the other users. But with rapid growth of technologies, data in the cloud normally increases which questions its security in storing in the cloud. Hence the protecting the cloud data seeks the strong security levels to counterfeit the different cloud attack. This study suggests the strong encryption algorithm accompanied by the hybrid combination of the chaotic scroll and logistic maps to establish the high end security to the cloud data. The proposed model exhibits the following advantages over the other algorithms: 1) High dynamic key generation 2) ability to counterfeit the multiple attacks 3) High randomness encrypted data which can provide more confusion of hacking from the intruder’s insight. To prove the strength of the proposed model, comprehensive trials are conducted utilizing extensive experimentation of the NIST (National Institute of Science and technology) in which different statistical tests experiments were conducted to validate the robustness of the suggested model. Additionally, The Burrows-Abadi-Needham Logic (BAN) serves as a formal assessment mechanism to evaluate and scrutinize the suggested methodology’s security phase. Both the Profverif tool and AVISPA are employed for comprehensive validation of the given model. Also the randomness of the suggested model is assessed with the other residing algorithm in means of communication cost and randomness. Results demonstrates that the proposed model shows its ability to provide more potent protection to the cloud data than the other existing encryption algorithms.